2021
DOI: 10.32861/jac.81.12.19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Stability of in vitro Propagated Grapevine (Vitis vinifera L.) cv. Al-Bayadi

Abstract: Grapevine (Vitis vinifera L.) fruit crops are a significant source of antioxidants, fibre, and nutrients; all are vital for a healthy diet and play a key role in the economy of several advanced and developing countries. It is of great importance to generate true-to-type plant products using in vitro propagation system. Thus, somaclonal variations can multiply very rapidly which leads to loss of the main features of parent rootstocks. In this research, a mixture of three Polymerase Chain Reaction (PCR)-based mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…CDDP markers were summarised to be a consistent technique for the evaluation of genetic diversity and correlations among grapevine species. CDDP marker assays have successfully detected higher numbers of genetic variation between control and micropropagated samples of grapevines [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDDP markers were summarised to be a consistent technique for the evaluation of genetic diversity and correlations among grapevine species. CDDP marker assays have successfully detected higher numbers of genetic variation between control and micropropagated samples of grapevines [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In grapevines, the ideal concentration of BA for shoot multiplication ranged from 2.22 to 11.1 µM. Concentrations above this range inhibited shoot growth and promoted callus formation, reducing the number of shoots and nodes [28]. Another study reported that a BA concentration of 2.5 µM yielded the best results in terms of growth per explant, while concentrations higher than 2.5 µM decreased these values [42].…”
Section: Assessment Of the Impact Of Hormones On The Growth And Multi...mentioning
confidence: 99%
“…Additionally, in vitro plant propagation methods have been associated with the occurrence of somaclonal mutations [25][26][27]. Since grape is a perennial crop, genetic variations resulting from in vitro propagation can only be observed at maturity and fruiting stages [28]. Therefore, early detection of genetic variations in in vitro-raised plants is crucial.…”
Section: Introductionmentioning
confidence: 99%